2020
DOI: 10.3390/land9100365
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Grazing on the Temperature Regime of the Alas Soils of Central Yakutia

Abstract: There are numerous studies on the effect of grazing on the physical and chemical parameters of soils. However, the impact of grazing on the temperature regime of the alas soils in Central Yakutia is still poorly understood. This paper presents the results of long-term observations of the state of the soil-and-plant cover of thermokarst basins—i.e., alases—located in the Lena-Amga interfluve and actively used as pastureland. Observations of the process of the self-restoration of grass cover and changes in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The critical diameter of grain will become larger as vegetation coverage decreases and wind erosion intensity increases. Lower grazing pressure resulted in a large amount of vegetation which might have increased surface roughness and thus favored the deposition of fine soil particles carried by the wind [12,28]. This study showed that the grazing treatment decreased (p < 0.01) the amount of silt (2-50 µm) and increased (p < 0.05) the amount of fine sand (100-250 µm) of surface soil (0-10 cm) compared to long-term enclosing, which suggested that surface soil became coarser with long-term grazing in semi-arid grasslands of Inner Mongolia.…”
Section: Soil Physical Propertiesmentioning
confidence: 99%
“…The critical diameter of grain will become larger as vegetation coverage decreases and wind erosion intensity increases. Lower grazing pressure resulted in a large amount of vegetation which might have increased surface roughness and thus favored the deposition of fine soil particles carried by the wind [12,28]. This study showed that the grazing treatment decreased (p < 0.01) the amount of silt (2-50 µm) and increased (p < 0.05) the amount of fine sand (100-250 µm) of surface soil (0-10 cm) compared to long-term enclosing, which suggested that surface soil became coarser with long-term grazing in semi-arid grasslands of Inner Mongolia.…”
Section: Soil Physical Propertiesmentioning
confidence: 99%